Metode Penanggulangan Peredaran Narkotika Di Lembaga Pemasyarakatan Terhadap Narapidana Sebagai Upaya Mencapai Tujuan Pemidanaan (Studi di Lembaga Pemasyarakatan Klas I Tanjung Gusta Medan) - Manullang, Herlina; Esther, July; Jusnizar (Jurnal IUS Kajian Hukum dan Keadilan, 2023)
Almost fifty percent of the prison population is prisoners of narcotics, this situation is very worrying for the occurrence of drug abuse in prison. Overcrowding greatly affects the process of coaching prisoners, so it is likely that the expected goal of punishment will not be achieved. The nature of the type of research is normative juridical. The concept of coaching carried out to prisoners in prison is guided by Article 34 to Article 46 of Corrections Law No. 22 of 2022. The mentoring program for prisoners of drug abuse is carried out including personality coaching and independence coaching. Efforts to minimize the abuse of narcotics in prison are guided by Permenkumham No. 6 of 2013 relating to the Code of Conduct for Correctional Institutions and Detention Centers. Based on these regulations, efforts to minimize drug abuse in prisons are carried out with preventive and repressive actions. The obstacles faced by prisons in minimizing drug abuse in prisons include the unavailability of experts, obstacles from the community and the lack of infrastructure and facilities in carrying out the process of coaching prisoners.